Detection of Heat-Stressed Furnace Wall’s Areas Based on Results of Numerical Simulations of Thermal Flows - Popov V.V; Taylasheva T.S.; Lebedev V.M. (MATEC Web of Conferences, 2016)
In this paper, a numerical study of the formation of nitrogen oxides in the combustion chamber based on the model created by Mitchellom and Terbellom. The distribution of furnace temperature and the concentration of nitrogen oxides, as well as a comparison of numerical results with the data of field experiment.